Pager Mangkok Luwih Bakuh Tinimbang Pager Tembok: Negasi Sekuritas dalam Falsafah Jawa - Fibiona, Indra; Lestari, Siska Nurazizah (Warisan: Journal of History and Cultural Heritage, 2022)
Javanese community has a philosophy of "Pager Mangkok Luwih Bakuh Tinimbang Pager Tembok" which has the meaning that the pager mangkok (a good relationship with the neighbors) luwih bakuh (have a stronger defense) tinimbang pager tembok (rather than a wall fence / physical fence of the home environment). Over time, this philosophy has deteriorated due to individualistic attitudes. This study is a qualitative study using a socio-anthropological approach to reveal distortions caused by deterioration that occurs. The study uses data mining methods in the form of literature studies and in-depth interviews to find out in depth the process of deterioration of that philosophy. The results of the study showed that individuals who undermined the philosophy were caused by several factors, including economics and consumerism, pragmatism, technological and information flows and population density and diversity.